2021
DOI: 10.1093/jac/dkab406
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of HIV drug resistance in patients with suspected virological failure in North-Western Tanzania

Abstract: Background More than 15 million people in sub-Saharan Africa receive ART. Treatment failure is common, but the role of HIV drug resistance in treatment failure is largely unknown because drug resistance testing is not routinely done. This study determined the prevalence and patterns of HIV drug resistance in patients with suspected virological failure. Materials and methods A single high viral load of >1000 viral RNA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
3
6
0
Order By: Relevance
“…Consistent with a previous study reporting higher prevalence of TAMs in individuals on long-term ART (>36 months) from Ghana (Nii-Trebi et al, 2013), all the TAMs detected in this study were in individuals receiving ART for a minimum of 40 months. TAMs are reported to be common in individuals failing tenofovir disoproxil fumarate-based regimens in sub-Saharan Africa (Gregson et al, 2017;Henerico et al, 2022). Likewise, in this study, six out of the eight individuals with TAMs were on tenofovir disoproxil fumarate-based regimen.…”
Section: Discussionsupporting
confidence: 54%
“…Consistent with a previous study reporting higher prevalence of TAMs in individuals on long-term ART (>36 months) from Ghana (Nii-Trebi et al, 2013), all the TAMs detected in this study were in individuals receiving ART for a minimum of 40 months. TAMs are reported to be common in individuals failing tenofovir disoproxil fumarate-based regimens in sub-Saharan Africa (Gregson et al, 2017;Henerico et al, 2022). Likewise, in this study, six out of the eight individuals with TAMs were on tenofovir disoproxil fumarate-based regimen.…”
Section: Discussionsupporting
confidence: 54%
“…The high rates of HIVDR among adolescents are most likely due to prolonged NNRTIs and NRTIs exposure since childhood and ART adherence challenges. The most frequent NNRTI mutations found in the current study (K103N, Y181C/Y, G190A and A98G) are comparable to other studies, which included children <14 years and young adolescents 10–14 years [ 39 , 41 ]. The low genetic barrier to resistance of most NNRTIs [ 13 ] explain the study findings.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, in SSA, the PI DRMs frequencies are below 10% (21, 35, 44). Moreover, in SSA, the PI DRMs frequencies are below 10% [ 31 , 40 , 41 , 49 ], suggesting that ART failure is most likely due to suboptimal adherence. However, it was surprising that more than 85% of resistance mutations to PIs occurred in Brazilian children and adolescents who had a vertical transmission of HIV for unexplained reasons [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“… 33 In addition, it has also been documented that the T97A accessory mutation is associated with increased dolutegravir resistance in conjunction with other DRMs in INSTI-experienced patients. 34 Our study has shown that DRMs against dolutegravir in INSTI-naive patients are rare. However, it is possible to occur, as shown in a study conducted in Uganda, which detected major INSTI-associated mutations (E138T, E138K and T66I) in the sequences of 6/511 (1.2%) ART-naive individuals, and accessory mutations were observed in 145 sequences, which accounted for 24% of the 511 sequences.…”
Section: Discussionmentioning
confidence: 75%
“…These possibilities have also been described in some case reports in South Africa, Botswana and Uganda. 34 , 37 , 38 The inevitability of some emergent drug resistance against dolutegravir has also been explained by mutations outside the integrase gene, arising in patients receiving dolutegravir-containing regimens with no mutations in the integrase gene, 39 as well as by the role of natural polymorphisms. 33 , 40 …”
Section: Discussionmentioning
confidence: 99%